Lithium battery diaphragm and preparation method thereof
The existing lithium-ion battery separator is solved by using ceramic powder, polyvinyl alcohol (PVA) and nanocellulose crystals or sodium carboxymethylcellulose to form chemical bonds with crosslinking agents in lithium-ion battery separator. The problem is that higher high temperature resistance and wettability are achieved, and the safety and service life of the battery are enhanced.
Patent Information
- Application Number
- CN202411469212.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing lithium-ion battery separators are not resistant to high temperatures, resulting in loss of active substances, decreased battery capacity, excessive internal pressure, and even smoke and fire, affecting the normal use of the battery and endangering personal safety.
By mixing ceramic powder, polyvinyl alcohol (PVA), nanocellulose crystals (CNC) or sodium carboxymethylcellulose (CMC-Na) with crosslinking agents to form chemical bonds, a dense and stable three-dimensional crosslinking network is prepared in a form of a dense and stable three-dimensional crosslinking network. Structure, improves the high temperature resistance and wettability of the diaphragm.
It significantly improves the high temperature resistance, wetting ability and reduces surface tension of the diaphragm, extends the service life of the battery, and enhances the safety of the battery.
Smart Images

Figure CN119401055A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium battery separator and a preparation method thereof. Background Art
[0002] With the development of the times, new energy electric vehicles have gradually become an integral part of people's lives. As the power source of electric vehicles, the safety and endurance of lithium-ion batteries are the focus of scientific research. Lithium battery separators play an important role in lithium-ion batteries.
[0003] The safety of electric vehicles has become a focus of more attention. In the existing technology, lithium-ion battery separators are not resistant to high temperatures, which causes loss of active substances, reduction of battery capacity, excessive internal pressure of the battery, battery bulging, leakage, and even smoke and fire, affecting the normal use of the battery and endangering personal safety. Therefore, there is an urgent need to find a lithium battery separator with good high temperature resistance.
[0004] Lithium battery separators are crucial in lithium batteries. Conventional alumina coated separators have only average high temperature resistance and cannot meet the above requirements. Summary of the invention
[0005] In view of the deficiencies of the prior art, an object of the present invention is to provide a method for preparing a slurry.
[0006] Another object of the present invention is to provide a battery separator.
[0007] Another object of the present invention is to provide a slurry obtained by the above preparation method.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] A method for preparing a slurry comprises the following steps:
[0010] Step 1, mixing ceramic powder, polyvinyl alcohol (PVA), a first substance and a cross-linking agent until uniform, and drying to obtain a first powder, wherein the first substance is nanocellulose crystals (CNC) and / or sodium carboxymethyl cellulose (CMC-Na);
[0011] In step 1, the cross-linking agent is glutaraldehyde (GD).
[0012] In step 1, the particle size of the first powder is 400-600 nm.
[0013] In step 1, drying is performed until the moisture content is ≤ 0.8% (mass fraction).
[0014] In step 1, the ceramic powder is alumina and / or boehmite, and the particle size of the ceramic powder is 400-550 nm.
[0015] In step 1, ceramic powder, polyvinyl alcohol (PVA), a first substance and a cross-linking agent are mixed and stirred for 10 to 30 minutes until they are uniform.
[0016] Step 2, mixing the first powder, water and adhesive until uniform to obtain a slurry, wherein the ratio of polyvinyl alcohol (PVA), the first substance, the cross-linking agent, water, the ceramic powder and the adhesive is (1-2.5): (2.5-4): (0.2-0.5): (65-74.8): (15-20): (5-10) by mass.
[0017] In step 2, the adhesive is polyacrylate.
[0018] In step 2, the first powder and water are mixed until uniform to obtain a first solution, and the first solution and an adhesive are mixed until uniform, and ground to obtain a slurry.
[0019] In the above technical solution, the first powder and water are mixed, stirred at a rotation speed of 3100-3600 r / min and a revolution speed of 10-20 r / min for 10-15 min, and then ultrasonicated at a frequency of 5-7 kHz for 10-30 min until uniform.
[0020] In step 2, the first solution and the adhesive are mixed, and ultrasonicated for 10 to 30 minutes under stirring conditions until they are uniform. The stirring rotation speed is 1000 to 1800 r / min, the revolution speed is 10 to 20 r / min, and the ultrasonic frequency is 5 to 7 kHz.
[0021] In step 2, the grinding speed is 400-600 r / min, and the grinding time is 10-15 min.
[0022] The slurry obtained by the above preparation method.
[0023] A diaphragm is obtained by coating the slurry on a base film and drying it.
[0024] Application of polyvinyl alcohol (PVA), nanocellulose crystals (CNC) and ceramic powders to synergistically improve the wettability of membranes.
[0025] Application of polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC-Na) and ceramic powder in synergistically improving the wettability of diaphragms.
[0026] Application of polyvinyl alcohol (PVA), nanocellulose crystals (CNC) and ceramic powders in synergistically improving the capacity retention rate of lithium batteries.
[0027] Application of polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC-Na) and ceramic powder in synergistically improving the capacity retention rate of lithium batteries.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention first forms chemical bonds between polyvinyl alcohol (PVA) and a first substance (nanocellulose crystals and / or sodium carboxymethyl cellulose) and ceramic powder by chemical crosslinking using a crosslinking agent, thereby obtaining a dense and stable three-dimensional crosslinked network structure, reducing the solubility of the diaphragm in water, and effectively improving the high temperature resistance, wetting ability and surface tension reduction of the diaphragm. A large number of hydroxyl groups on the surface of the first substance and hydroxyl groups on the polyvinyl alcohol (PVA) molecular chain can form intermolecular hydrogen bonds, promote crystallization, and restrict the movement of the polyvinyl alcohol (PVA) molecular chain, thereby improving the high temperature resistance, wetting ability and surface tension reduction of the diaphragm (PVA-ceramic-CNC composite diaphragm). BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a distribution diagram of the diaphragm prepared from the slurry of Example 1 under a scanning electron microscope at 5KX;
[0031] Figure 2 This is a distribution diagram of the diaphragm prepared from the slurry of Example 1 under a scanning electron microscope at 15KX;
[0032] Figure 3 This is a distribution diagram of the diaphragm prepared from the slurry of Example 4 under a scanning electron microscope at 5KX;
[0033] Figure 4 This is a distribution diagram of the diaphragm prepared from the slurry of Example 4 under a scanning electron microscope at 15KX. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0035] The materials used in the specific implementation of the present invention are as follows:
[0036] Aluminum oxide is an inorganic substance with the chemical formula Al2O3. It is a high hardness compound with a melting point of 2054℃ and a boiling point of 2980℃.
[0037] Boehmite, also known as diaspore, has the molecular formula γ-AlOOH (hydrated aluminum oxide) and decomposes above 400°C.
[0038] Cellulose nanocrystals (CNC) are a cellulose derivative with excellent properties such as large specific surface area, high crystallinity, strong hydrophilicity, high strength, large elastic modulus, and rich functional groups.
[0039] Polyvinyl alcohol (PVA) is a biodegradable water-soluble polymer with excellent film-forming properties, good thermal stability and high crystallinity.
[0040] Sodium carboxymethyl cellulose (CMC-Na) is an organic substance, a carboxymethyl derivative of cellulose, and the most important ionic cellulose gum. Sodium carboxymethyl cellulose is usually an anionic polymer compound prepared by the reaction of natural cellulose with caustic soda and monochloroacetic acid. CMC-Na is a white fibrous or granular powder, odorless, tasteless, hygroscopic, and easily dispersed in water to form a transparent colloidal solution.
[0041] In the following examples, water is deionized water.
[0042] In the following embodiments, the base film is a PE film, and the thickness of the base film is about 7 μm.
[0043] In the following examples, the polyacrylate is polymethyl acrylate.
[0044] The size of the nanocellulose crystals used in the following examples is 0.01-0.02 μm.
[0045] In the following embodiments, the electrolyte is a mixture of an electrolyte and a solvent, the electrolyte in the electrolyte is LiPF6, the solvent is a mixture of EC (ethylene carbonate) and DMC (dimethyl carbonate), the volume ratio of ethylene carbonate and dimethyl carbonate is 1:1, and the concentration of the electrolyte in the electrolyte is 1 mol / L.
[0046] Example 1
[0047] A method for preparing a slurry comprises the following steps:
[0048] Step 1, in a reaction kettle, ceramic powder, polyvinyl alcohol (PVA), a first substance and a cross-linking agent are mixed at 25° C., stirred for 30 minutes until uniform, filtered, dried (dried to a moisture content of 0.8% (mass fraction)), crushed, and sieved to obtain a first powder with a particle size of 400 to 600 nm, wherein the first substance is nanocellulose crystals (CNC), the cross-linking agent is glutaraldehyde (GD), the ceramic powder is alumina (particles), and the particle size of the alumina (particles) is 400 to 500 nm;
[0049] Step 2, in a double planetary mixer, mix the first powder and water, stir at a rotation speed of 3100r / min and a revolution speed of 20r / min for 10min, and then ultrasonicate at a frequency of 5kHz for 10min until uniform, to obtain a first solution, mix the first solution and the adhesive, ultrasonicate for 30min under stirring conditions until uniform (the stirring rotation speed is 1000r / min, the revolution speed is 20r / min, and the frequency of ultrasound is 5kHz), put into a grinder, and grind at a speed of 400r / min for 10min to obtain a slurry, in which the ratio of polyvinyl alcohol (PVA), the first substance, the crosslinking agent, water, the ceramic powder and the adhesive is 2.5:2.5:0.2:74.8:15:5 by mass, and the adhesive is polyacrylate.
[0050] Example 2
[0051] A method for preparing a slurry is basically the same as that of Example 1, except that "the first substance is nanocellulose crystals (CNC)" is replaced by "the first substance is sodium carboxymethyl cellulose (CMC-Na)".
[0052] Example 3
[0053] A method for preparing a slurry comprises: mixing ceramic powder, a first substance and water in a double planetary mixer, stirring for 10 minutes at a rotation speed of 3100 r / min and a revolution speed of 20 r / min, then ultrasonicating for 10 minutes at 3 kHz, adding an adhesive, ultrasonicating for 30 minutes under stirring conditions until uniform (the stirring rotation speed is 1000 r / min, the revolution speed is 20 r / min, and the frequency of the ultrasound is 5 kHz), putting into a grinder, grinding at a speed of 400 r / min for 10 minutes to obtain a slurry, wherein the ratio of the first substance, water, ceramic powder and adhesive is 5:75:15:5 by mass, the adhesive is polyacrylate, the first substance is sodium carboxymethyl cellulose (CMC-Na), the ceramic powder is aluminum oxide (particles), and the particle size of the aluminum oxide (particles) is 400-500 nm.
[0054] Example 4
[0055] A method for preparing a slurry is basically the same as that of Example 1, except that "the ceramic powder is alumina (particles)" is replaced by "the ceramic powder is boehmite (particles)". The particle size of the boehmite (particles) is 450-550 nm.
[0056] Example 5
[0057] A method for preparing a slurry is basically the same as that of Example 2, except that "the ceramic powder is alumina (particles)" is replaced by "the ceramic powder is boehmite (particles)". The particle size of the boehmite (particles) is 450-550 nm.
[0058] Example 6
[0059] A method for preparing a slurry is basically the same as that of Example 3, except that "the ceramic powder is alumina (particles)" is replaced by "the ceramic powder is boehmite (particles)". The particle size of the boehmite (particles) is 450-550 nm.
[0060] Embodiments 7 to 12
[0061] A lithium battery, comprising: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode material in the positive electrode is a ternary material (NCM523), the negative electrode material in the negative electrode is graphite, the positive electrode slurry is a mixture of N-methylpyrrolidone, the positive electrode material, conductive carbon black and a positive electrode binder (polyvinylidene fluoride, PVDF), and the ratio of N-methylpyrrolidone, the positive electrode material, the conductive carbon black and the positive electrode binder (PVDF) in the positive electrode slurry is 10:8:1:1 by weight, and the negative electrode slurry is a mixture of N-methylpyrrolidone, graphite, a conductive agent (ketjen black) and a negative electrode binder (styrene butadiene latex, SBR), and the ratio of N-methylpyrrolidone, the positive electrode material, the conductive carbon black and the positive electrode binder (PVDF) in the negative electrode slurry is 10:8:1:1 by weight. The ratio of ketone, graphite, conductive agent (ketjen black) and negative electrode binder (styrene butadiene latex, SBR) is 10:8:0.8:1.2. The preparation method of the positive electrode includes: mixing N-methylpyrrolidone, NCM523, conductive carbon black and positive electrode binder by a wet process, stirring at a rotation speed of 1500r / min and a revolution speed of 20r / min, and then ultrasonicating at a frequency of 7kHz for 30min to obtain positive electrode slurry, coating 1.5g of the positive electrode slurry on an aluminum foil substrate (91.5mm*1m), drying in a constant temperature oven to form a positive electrode coating on the aluminum foil substrate, and rolling to firmly press the positive electrode coating and the aluminum foil substrate to obtain a positive electrode. The preparation method of the negative electrode includes: mixing N-methylpyrrolidone, graphite, conductive agent (ketjen black) and negative electrode binder by wet process, stirring at a rotation speed of 1500r / min and a revolution speed of 20r / min, and then ultrasonicating at a frequency of 7kHz for 30min to obtain negative electrode slurry. 1.5g of negative electrode slurry is coated on a copper foil substrate (91.5mm*1.2m), dried in a constant temperature oven, a negative electrode coating is formed on the copper foil substrate, and roller pressing is performed to firmly press the negative electrode coating and the copper foil substrate to obtain a negative electrode. The method for preparing a diaphragm includes: applying the slurry to the base film by roller coating, drying at 45°C for 10min, obtaining a coating on the base film, and obtaining a diaphragm. The slurry is one of the slurries prepared in Examples 1 to 6. The lithium batteries of Examples 7 to 12 are prepared in sequence from the slurries in Examples 1 to 6.
[0062] Table 1
[0063]
[0064]
[0065] Figure 1 This is an electron microscope image of the diaphragm prepared from the slurry of Example 1 at 5KX. Figure 2 This is an electron microscope image of the diaphragm prepared from the slurry of Example 1 under 15KX.
[0066] Figure 3 This is an electron microscope image of the diaphragm prepared from the slurry of Example 4 at 5KX. Figure 4 The electron microscope image of the diaphragm prepared from the slurry of Example 4 under 15KX.
[0067] The diaphragms prepared from the slurries of Examples 1 to 6 were tested under standard atmospheric conditions, namely, temperature: 20° C.; relative humidity: 50%; atmospheric pressure: 96 kPa. The test results are shown in Table 2.
[0068] Table 2
[0069] Lithium battery separator Contact angle of electrolyte (°) Example 7 0.89 Example 8 1.10 Example 9 1.56 Example 10 0.97 Embodiment 11 1.06 Example 12 1.63
[0070] It can be seen from Table 2 that the contact angle of the diaphragm prepared in Example 7 is 0.89°, which is much smaller than the contact angles of the diaphragms prepared in Examples 8 to 12. Therefore, the diaphragm prepared from the slurry of Example 1 has better wettability.
[0071] Table 3
[0072]
[0073] As shown in Table 3, the thermal shrinkage (150°C / 1H) longitudinal (MD) and transverse (TD) shrinkage rates of the separator prepared in Example 7 of the present invention are both within 2.5%, which is better than that of Examples 8 to 12. The separator prepared from the slurry of Example 1 has better thermal stability.
[0074] The capacity retention data of the lithium batteries prepared in Examples 7 to 12 are shown in the following table (three parallel experiments were conducted for each example).
[0075] Table 4
[0076]
[0077] Example 7 The lithium battery prepared at J = 25.97A / m 2 After more than 200 cycles at the current density, the capacity retention rate can still be maintained above 94%.
[0078] The test data of the lithium battery separator prepared in Example 7 are as follows:
[0079]
[0080]
[0081] The test data of the lithium battery separator prepared in Example 10 are as follows:
[0082]
[0083] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a slurry, characterized in that: The following steps are involved: Step 1, mixing ceramic powder, polyvinyl alcohol, a first substance and a cross-linking agent until uniform, and drying to obtain a first powder, wherein the first substance is nanocellulose crystals and / or sodium carboxymethyl cellulose; Step 2, mixing the first powder, water and adhesive until uniform to obtain a slurry, wherein the ratio of polyvinyl alcohol, the first substance, the cross-linking agent, water, ceramic powder and adhesive is (1-2.5): (2.5-4): (0.2-0.5): (65-74.8): (15-20): (5-10) by mass.
2. The preparation method according to claim 1, characterized in that: In step 1, the cross-linking agent is glutaraldehyde.
3. The preparation method according to claim 1, characterized in that: In step 1, the ceramic powder is alumina and / or boehmite, and the particle size of the ceramic powder is 400-550 nm.
4. The preparation method according to claim 1, characterized in that: In step 2, the adhesive is polyacrylate.
5. The slurry obtained by the preparation method according to any one of claims 1 to 4.
6. A diaphragm, characterized in that: The slurry according to claim 5 is coated on a base film and then dried to obtain the product.
7. Use of polyvinyl alcohol, the first substance and ceramic powder to synergistically improve the wettability of the diaphragm / the heat resistance of the diaphragm / the battery capacity retention rate.
8. The use according to claim 7, characterized in that In terms of mass fractions, the ratio of polyvinyl alcohol, the first substance and the ceramic powder is (1-2.5): (2.5-4): (15-20).
9. A diaphragm, characterized in that: include: The base film and the coating include: ceramic powder, polyvinyl alcohol and a first substance, the first substance is nanocellulose crystals and / or sodium carboxymethyl cellulose, the polyvinyl alcohol and the first substance are chemically cross-linked by a cross-linking agent, and then chemical bonds are formed with the ceramic powder to form a three-dimensional cross-linked network structure.
10. The diaphragm according to claim 9, characterized in that In terms of mass fractions, the ratio of polyvinyl alcohol, the first substance, the cross-linking agent, and the ceramic powder is (1-2.5): (2.5-4): (0.2-0.5): (15-20).
Citation Information
Patent Citations
Aqueous slurry for lithium battery coating membrane, lithium battery coating membrane and preparation methods of aqueous slurry and lithium battery coating membrane
CN107611320A
Preparation method of low-temperature-resistant inorganic diaphragm type lithium ion battery, battery cell and lithium ion battery
CN109755440A
Integrated lithium battery coating diaphragm with cohesiveness
CN111312969A
Production of ceramic porous body
JP1992202071A
KR20210094819A
Cited By
Water-based ceramic lithium battery coating slurry and preparation method thereof
CN120149729A